Self-esteem and organizational commitment in employees of a provincial public university - Loli Pineda, Alejandro (2007)
The study attempts to examine the relationship that exists between self-esteem and the organizational commitment of administrative workers within a provincial public university using a sample of 48 subjects, representing 18% of the total university population. The study shows that a relationship between self-esteem and organizational commitment does not exist; however, we found that a correlation exists between self-esteem and factors related to organizational commitment, specifically commitment to work.